Whole exome sequencing and bioinformatics reveal PMAIP1 and PDGFRL as immune-related gene markers in follicular thyroid carcinoma - Wang, Haobo; Shang, Fangjian; Jiang, Xia; Li, Zhongxin; Li, Dongyun; Zhou, Chuanmin; Pang, Bo; Kang, Longfei; Liu, Bo; Zhao, Zengren (Frontiers in Genetics, 2025)
IntroductionThe primary clinical challenge associated with follicular thyroid carcinoma (FTC) lies in accurately diagnosing the condition, particularly in distinguishing it with follicular thyroid adenoma (FTA) due to their overlapping cytomorphological features and sonographic characteristics.MethodsWhole exome sequencing (WES) techniques and Gene Expression Omnibus (GEO) database were utilized to analyze genomic difference between FTC and FTA, with a specific focus on immune-related genes. The hub genes were subjected to enrichment analysis, immune infiltration analysis, protein-protein interaction (PPI) analysis, and receiver operating characteristic (ROC) curve analysis. Then utilized quantitative real-time polymerase chain reaction (qRT-PCR) and immunohistochemistry (IHC) to validate the expression levels of PMAIP1 and PDGFRL at the cellular and tissue levels.ResultsThe findings of WES and bioinformatics analysis indicated that PMAIP1 and PDGFRL were potential mutated immune-related genes in FTC, in comparison to FTA, the expression of PMAIP1 is up-regulated in FTC while PDGFRL is down-regulated, demonstrating promising diagnostic efficacy. Enrichment analysis and immune infiltration analysis suggested that PMAIP1 and PDGFRL may serve as potential therapeutic targets for FTC. The results of the validation at both cellular and tissue levels indicated an up-regulation of PMAIP1 and a down-regulation of PDGFRL in FTC, consistent with the results from bioinformatics analysis. DiscussionIn conclusion, it is the first research to revealed PMAIP1 and PDGFRL as potential novel immunodiagnostic markers for FTC, shedding light on their potential biological significance in this context, and offering potential valuable clinical applications.